28 = 6x - 4y

To rewrite the equation so that y is a function of x, we have to get y by itself.

Step 1: Move the x term to the other side

To move the x term to the other side we have to subtract it. 6x is positive and subtraction is the opposite of addition. What we do to one side we have to do to the other to keep both sides even.

`28-6x = 6x-4y-6x`

`28-6x = -4y`

Step 2: Move the number connected to the y term

The -4 is being multiplied by y, so to get rid of it we have to do the opposite operation which is division. We have to divide both sides and all terms by -4.

`(28/-4)-((6x)/-4) = ((-4y)/-4)`

`-7+3/2 x =y`

`y=3/2x-7`

`28=6x-4y`

To show that y is a function of x, the y should be isolated. So move the 6x to the other side of the equation.

`28-6x=6x - 6x - 4y`

`28- 6x = 0 - 4y`

`28-6x=-4y`

And, divide both sides by -4.

`(28-6x)/(-4)=(-4y)/(-4)`

`28/(-4)-(6x)/(-4) = y`

`-7 + (3x)/2=y`

`(3x)/2-7=y`

**Re-writing the given equation as y a function of x, it becomes `y =(3x)/2 - 7` .**

1. 28 = 6x - 4y

2. 28-6x=-4y

3. (28-6x)/-4=y

4. -7+(3/2x)=y

5. (3/2x) - 7 = y

Bring variable *y* to one side,

`4y = 6x - 28`

Divide both sides to make variable *y* alone,

`y =(6x - 28)/(4)`

Further simplify the equation, we get

`y =(3x)/(2) - 7`

Given ,

# 28 = 6x - 4y

As all the coefficients are even numbers ,so they are divisible by 2 . By dividing with 2 we get

14 =3x-2y

=> Again divide the present equation by 2 so we get

7=(3/2) x-y

=> 7+y= (3/2) x

=> now we can rewrite the above equation as

y= (3/2) x -7

simple :)

**Original equation: 28 = 6x - 4y**

1) Put the *y *variable on one side, and the others on the other:

4y = 6x - 28

2) Divide *y *by 4:

y = (6x - 28)/4

3) Simplify:

y = 3x/2 - 7

Rewriting an equation so that y is a function of x is the same as saying "find y in terms of x". You want to essentially solve for y.

First rewrite so that all the y terms are on one side.

4y = 6x - 28

Then solve for y.

`y = (6x)/4 - 28/4`

`y = (3x)/2 - 7`

` `